2013
DOI: 10.1371/journal.pone.0066441
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the R2 Retrotransposon Ribozyme and Its Self-Cleavage Site

Abstract: R2 is a non-long terminal repeat retrotransposon that inserts site-specifically in the tandem 28S rRNA genes of many animals. Previously, R2 RNA from various species of Drosophila was shown to self-cleave from the 28S rRNA/R2 co-transcript by a hepatitis D virus (HDV)-like ribozyme encoded at its 5' end. RNA cleavage was at the precise 5' junction of the element with the 28S gene. Here we report that RNAs encompassing the 5' ends of R2 elements from throughout its species range fold into HDV-like ribozymes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 47 publications
6
31
0
Order By: Relevance
“…Consistent with this model, in all animals the junctions of 5’ truncated R2 insertions, which are generated when the reverse transcriptase doesn't reach the 5’ end of the RNA template, are found to involve microhomologies and non-templated additions (84,87,94). Direct support for this model has also been provided by in vivo R2 injection experiments in Drosophila, which yielded integrations with precise 5’ junctions when the injected R2 RNA contained upstream 28S sequences and highly variable junctions when the injected R2 RNA did not contain upstream 28S sequences (74).…”
Section: Mechanism Of R2 Integrationsupporting
confidence: 55%
See 3 more Smart Citations
“…Consistent with this model, in all animals the junctions of 5’ truncated R2 insertions, which are generated when the reverse transcriptase doesn't reach the 5’ end of the RNA template, are found to involve microhomologies and non-templated additions (84,87,94). Direct support for this model has also been provided by in vivo R2 injection experiments in Drosophila, which yielded integrations with precise 5’ junctions when the injected R2 RNA contained upstream 28S sequences and highly variable junctions when the injected R2 RNA did not contain upstream 28S sequences (74).…”
Section: Mechanism Of R2 Integrationsupporting
confidence: 55%
“…An analysis of R2 from many other animals spanning its entire host range revealed that the 5’ end of all R2 elements could be folded into an HDV-like ribozyme structure (84). Comparison of these different R2 ribozymes revealed considerable flexibility in some aspects of the structure and in the sequence.…”
Section: Mechanism Of R2 Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…7B, which shows similar steps in R2Ol). The self-cleavage site in most R2 elements from different species was shown not at the 5′ end of the element but at 28S sequences up to 36 nucleotides upstream of the 5′ junction (98). It has been postulated that the cotranscribed 28S sequences of the first cDNA strand at the 5′ junction may anneal to the target site and prime the synthesis of the second DNA strand (98).…”
Section: Mrna/target Dna Interactionmentioning
confidence: 99%